Gold and international liquidity : the flow of credit in relation to gold in the international monetary system - Busschau, William John. (Johannesburg : South African Instutute of International Affairs, 1961)
This book is about the flow of fund in relation to gold in the international monetary system.
Include index
with bibliographical references
oo 31/7/18
Loans
Keywords: Gold standard; Foreign exchange